Reproducibility of the disordered vortex structure in twinned single crystals of YBCO - Nieva, Gladys; Herbsommer, J.A.; Nieva, G.; Luzuriaga, J. (Elsevier, 2000)
Fil: Herbsommer, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina